2018
DOI: 10.1371/journal.pone.0201814
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence victimization increases the risk of under-five morbidity: A stratified multilevel analysis of pooled Tanzania Demographic Health Surveys, 2010-2016

Abstract: IntroductionA hidden determinant such as intimate partner violence victimization has been associated with under-five morbidity and mortality. However, there is lack of information regarding which exactly age group of under-five is more vulnerable to morbidity when their mothers exposed to intimate partner violence victimization. This study aimed to determine the effect of mothers’ exposure to intimate partner violence victimization on age groups specific under-five morbidity that could lead to mortality.Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 50 publications
(63 reference statements)
5
11
0
Order By: Relevance
“…Our study supports the ndings of a study in South Asia where they found that IPV against women was a predisposing factor for child cough, malaria and diarrhea (32). In Tanzania, a nationally representative study also found that children of mothers who were exposed to any form of IPV were at high risk of suffering from fever, cough and diarrhea (33). Two explanations can be offered for the observed association between controlling behaviour IPV and child malaria.…”
Section: Discussion and Implicationsupporting
confidence: 90%
“…Our study supports the ndings of a study in South Asia where they found that IPV against women was a predisposing factor for child cough, malaria and diarrhea (32). In Tanzania, a nationally representative study also found that children of mothers who were exposed to any form of IPV were at high risk of suffering from fever, cough and diarrhea (33). Two explanations can be offered for the observed association between controlling behaviour IPV and child malaria.…”
Section: Discussion and Implicationsupporting
confidence: 90%
“…Unlike prior studies of associations with diarrhoea and ARI,19–23 we examined the impacts of emotional violence and assessed associations according to clearly delineated types of IPV. Notably, our exploration of maternal experience of emotional violence alone was related to increased odds of children’s diarrhoea, ARI or fever.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer studies have addressed impacts beyond infancy, but some studies indicate that stunting, wasting or underweight physical status,14 15 under 5 years mortality16 17 and asthma18 are associated with maternal IPV victimisation. Several studies in low-income and middle-income countries have found associations with diarrhoea and acute respiratory infection (ARI) 19–23. These illnesses, which remain leading causes of childhood mortality in low-income and low-middle-income countries, account for roughly a quarter of childhood deaths under 5 years 24.…”
Section: Introductionmentioning
confidence: 99%
“…There is also growing evidence that IPV and child maltreatment can co-occur within households and produce intergenerational effects 7–9. Children of mothers experiencing IPV are under a higher risk of under-five mortality, poor growth and development, as well as to an increased risk of perpetrating or experiencing IPV against women later in life 10–13…”
Section: Introductionmentioning
confidence: 99%